2019
DOI: 10.3390/metabo9060112
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Changes of Plasma Metabolome in Response to Severe Feed Restriction in Pregnant Ewes

Abstract: Maternal metabolic disorders in ewes induced by energy deficiency have a detrimental effect on the maternal health and lambs. However, the dynamic processes of metabolic disorders are unknown. Therefore, this study attempted to explore the dynamic changes of maternal metabolism based on metabolomics approach during energy deficiency in pregnant ewes. Twenty pregnant Hu sheep were fed a basic diet or a 70% restricted basic diet. The HPLC-MS platform was applied to identify blood metabolites. Principal component… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 25 publications
2
11
0
Order By: Relevance
“…These results suggested that maternal undernutrition may lead to programmed hepatic metabolism and the programming effect didn’t observe in a short time (fetal phase) but appeared after a long time (kid phase). Guo et al (2019) observed that citrate cycle was significantly suppressed by severe feed restriction in sheep with lower level of glucose-6-phosphate, citrate and -ketoglutarate in the blood sample. Milk replacer restriction downregulated the expression of isocitrate dehydrogenase 2 ( IDH2 ) and oxoglutarate dehydrogenase complex (OGDH) which involved in citrate cycle of lambs ( Santos et al, 2018b ).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…These results suggested that maternal undernutrition may lead to programmed hepatic metabolism and the programming effect didn’t observe in a short time (fetal phase) but appeared after a long time (kid phase). Guo et al (2019) observed that citrate cycle was significantly suppressed by severe feed restriction in sheep with lower level of glucose-6-phosphate, citrate and -ketoglutarate in the blood sample. Milk replacer restriction downregulated the expression of isocitrate dehydrogenase 2 ( IDH2 ) and oxoglutarate dehydrogenase complex (OGDH) which involved in citrate cycle of lambs ( Santos et al, 2018b ).…”
Section: Discussionmentioning
confidence: 89%
“…These results suggested that maternal undernutrition may lead to programmed hepatic metabolism and the programming effect didn't observe in a short time (fetal phase) but appeared after a long time (kid phase). Guo et al (2019) et al, 2018b). These results were similar to the results of our study that feed restriction downregulated citrate cycle on transcriptome with lower expression of succinate dehydrogenase complex subunit C (SDHC) and IDH1.…”
Section: Hepatic Metabolism In Fetal and Kid Goats Undergone Maternal Undernutritionmentioning
confidence: 99%
“…The calculated p value was established based on pathway enrichment analysis, and the pathway impact value was based on pathway topology analysis. The most relevant metabolic pathways were the retinol metabolic pathway, porphyrin and chlorophyll metabolic pathway, and steroid hormone biosynthesis pathway | 9 PEDIATRIC UROLITHIASIS SERUM METABOLOMICS F I G U R E 5 Metabolic pathways and metabolites associated with pediatric urolithiasis. (a) Schematic of abnormal metabolic pathways in patients with urolithiasis.…”
Section: Discussionmentioning
confidence: 99%
“…Data acquisition was performed according to the prior study. 9 The 10 μl of the supernatant were injected into the LC‐MS (Ultimate 3000 LC, Q Exactive; Thermo Scientific) in random order. A reverse‐phase 2.1*100 mm 1.9 μm C18 column (Hyper gold) was used for separation.…”
Section: Methodsmentioning
confidence: 99%
“…Lipids, as physiological fuels, are stored in adipose tissue with low water content and high energy density [45]. Humans and animals usually break down fat to meet their energy requirements when the energy supply is restricted.…”
Section: Fat Metabolism-relatedmentioning
confidence: 99%